Kajian Efektifitas Penggunaan Abu Sekam Padi sebagai Bahan Stabilisasi pada Tanah Lempung terhadap Nilai CBR - Vella Anggreana; Rasyidah Rasyidah (Pusat Riset dan Inovasi Nasional, 2024)
One type of soil that has many problems in a construction development is clay soil. Clay soil originating from Jl. Abdul Rahman Hamid, Tenayan Raya District, Pekanbaru has a problem where there are cracks and waves on the road due to non-uniform subsidence. To deal with problems in the soil one way that can be done is by stabilization. The purpose of this study was to determine to determine the effect of a mixture of rice husk ash on the CBR value and to find the optimal mixture. The research uses the laboratory test method, by testing CBR on variations of the rice husk ash mixture amounting to 4%, 7%, and 10% of the dry weight of the soil with unfermented conditions, 7 days of incubation and 4 days of soaking. The effect of using rice husk ash on the value of CBR in unfermented conditions increased in the 4% and 7% rice husk ash mixture, but decreased in the 10% rice husk ash mixture. The influence of the use of rice husk ash mixture on 7-day fermentation increases the CBR values. Whereas in immersion conditions, the CBR value tends to decrease with increasing rice husk ash levels. The optimal mixture in CBR occurred in a mixture of 10% rice husk ash with a 7-day fermentation condition of 12.85%. Thus, it is concluded that the use of the percentage of the mixture as well as the length of the soaking and soaking days used can affect the CBR value of the soil.